Learning Pixelmator. - Stagi, Mark (Packt Publishing, 2003)
A fast paced, example driven approach to learning Pixelmator.""Learning Pixelmator"" is great for photographers of any level who are looking to learn to take advantage of Pixelmator to edit images. Without any prior knowledge of image editing software needed, we will start with the basics and move onto more advanced image editing techniques. No matter what your current artistic level is, this book will give you the power to unleash the artist within!